Continuous-discrete estimation of stochastic processes over memory (time-delay) observations with anomalous noises; IFAC Proceedings Volumes; Vol. 16, Iss. 1 - Rozhkova S. V. Svetlana Vladimirovna (2006, 2006)
The joint synthesis of mean square optimal (MSO) unbiased filter-interpolator-extrapolator (FIE) is performed. It is supposed that these processes depend not only on the current values of an unobserved process but on an arbitrary number of its preceding values, and anomalous noise occurs in discrete observations. The properties of MSO FIE are investigated..